Biological explanations of criminal behavior - Ling, Shichun (Psychology, crime & law, 2019)
There is a growing literature on biological explanations of antisocial and criminal behavior. This paper provides a selective review of three specific biological factors - psychophysiology (with the focus on blunted heart rate and skin conductance), brain mechanisms (with a focus on structural and functional aberrations of the prefrontal cortex, amygdala, and striatum), and genetics (with an emphasis on gene-environment and gene-gene interactions). Overall, understanding the role of biology in antisocial and criminal behavior may help increase the explanatory power of current research and theories, as well as inform policy and treatment options.